An Asset Allocation Puzzle: Comment - Shalit, Haim; Yitzhaki, Shlomo (American Economic Review, 2003)
The purpose of this note is to look at the rationale behind popular advice on portfolio allocation among cash, bonds, and stocks. We argue that the typical investment advice is not inconsistent with the behavior of risk-averse expected-utility maximizers. We propose an additional solution to the asset allocation puzzle posed by Niko Canner et al. (1997), who argue that popular advice contradicts financial theory because it is inconsistent with the capital asset pricing model (CAPM) mutual-fund separation theorem. The CAPM asserts that investors should hold the same selection of risky assets, while popular advice is that investors should hold a proportion of bonds to stocks that increases with risk aversion. Using mean-variance (MV) analysis and the CAPM, Canner et al. show that recommended portfolios are far from optimal and that losses from the apparent failure of optimization are not substantial. However, they failed to explain the popular advice within an economic model. We offer a rational model based on stochastic dominance to demonstrate that all popular financial advice portfolios belong to the efficient set for all risk-averse investors. Using the historical annual real returns on bonds and stocks in Canner et al., we cannot ascertain that investment advisors indeed offer bad advice. Rather, we maintain that acting as agents for numerous clients, advisors recommend portfolios that are not inefficient for all risk-averse investors. I. Overview